RAYLEIGH SURFACE WAVE ANALYSIS AND APPLICATION AT THE MONFALCONE LANDFILL, AND AT THE INDUSTRIAL AREA OF PORTO PETROLI, GENOA, NORTHERN ITALY - Κρητικάκης, Σ. Γ.; Βαφείδης, Α.; Gourry, J. C. (Bulletin of the Geological Society of Greece, 2004)
During the last few years, the dispersion of Rayleigh surface waves has been intensively studied as an alternative to contemporary geotechnical and environmental geophysical techniques. Nowadays, Rayleigh surface wave analysis (SASW, MASW) is widely used for the determination of S-wave velocity distribution with depth. This work aims to the description of the Rayleigh surface wave analysis methodology as well as to the presentation of its application on seismic data from geophysical surveys, carried out for the purposes of the HYGEIA European project, in two polluted areas: a) In the area of Monfalcone, northern Italy and b) in the industrial area of Porto Petroli, Genoa. Rayleigh surface wave analysis proved very useful in locating the lateral and vertical extent of the heterogeneous soil in Monfalcone and in mapping the bedrock relief in Porto Petroli through Swave velocity determination.